Microstructure and mechanical properties of AlMgSi alloys after equal channel angular pressing at room temperature - Chang, JY; Shan, A (ELSEVIER SCIENCE SA, 2003)
Equal channel angular (ECA) pressing up to four passes was conducted on as-solution-treated AlMgSi alloy at room temperature. The alloy work piece was failed after the second pass owing to rapid hardening. Four ECA pressing passes could be successfully performed without any cracking by introducing intermediate annealing at 200 degreesC for an hour after the second pass. Ultrafine microstructure with grain size of about 0.5 mum was obtained after four ECA pressing passes. Tensile strength was significantly improved after two passes of ECA pressing while reasonable ductility was maintained. Tensile strength decreased with intermediate annealing, and additional two ECA pressing passes after intermediate annealing did not increase the tensile strength. High density of dislocations was found inside grains after four repetitive ECA pressings. It is suggested that the high strength of the alloy was resulted from both the high density of dislocation and fine grain sizes. (C) 2002 Published by Elsevier Science B.V.
Keywords: GRAINED MATERIALS; REFINEMENT; ALUMINUM